The linkage between strategy, strategic groups, and performance in the U.K. retail grocery industry - Lewis, P (Institutional Knowledge at Singapore Management University, 1990)
This paper focuses upon the performance consequences of strategic group membership in a specific context, namely, the U.K. retail grocery industry. Alternative grouping procedures indicate that performance differences exist across groups-in line with theoretical expectations-for some of the multiple indicators of performance used in the study, specifically ROS (return on sales) but not ROCE (return on capital employed) or PER (price-earnings ratio). A discriminant analysis model demonstrates that the strategic dimensions identified from in-depth industry analysis are good performance discriminators. The results generally indicate that strategic groups are useful constructs for studying industry structure and competitive strategy, but that they generally do not explain performance differences. This is in line with the results of more recent studies, e.g. Cool and Schendel (1987) and Fiegenbaum (1987), which show limited evidence of performance differences suggesting perhaps that the unit of analysis for examining performance differences should be at the level of the firm. The study also shows that there are consistent patterns present in the positioning of the main strategic groups within the industry.